La Contribución Del Análisis Institucional a Las Ciencias Sociales! - Polanyi, Karl (Revista de Economía Institucional, 2018)
El artículo presenta un discurso del autor en la Conferencia de la Sociedad de Postgrado de Economía de la Universidad de Colombia, Nueva York, en 1950, acerca del análisis institucional a las ciencias sociales. Comenta sobre la relación entre tales ramas de las ciencias sociales como la historia, la economía y la antropología. ENG: The article presents a speech by the author at the Conference of the Graduate Society of Economics of the University of Colombia, New York, in 1950, about the institutional analysis of the social sciences. Comment on the relationship between such branches of the social sciences such as history, economics and anthropology
Keywords: For a New West: Essays 1919-1958 (Book); POLANYI, Karl, 1886-1964; anthropology; anthropology & history; economics; ethnohistory; history & economics; original work; social science research; social sciences

Mercados, historia y teleología: reflexiones desde la noción de «doble movimiento» de Karl Polanyi - Polo Blanco, Jorge Polo (CONVIVIUM, 2018)
En el presente trabajo mostraremos que la filosofía liberal operó en muchas ocasionesa través de un esquema teleológico, desde el cual entendía que la espontaneidad delmovimiento histórico conducía de forma natural hacia una economía de mercados libres.Semejante interpretación tenía que presuponer otra controvertida tesis, a saber, que lascategorías que informan la racionalidad práctica dentro de una sociedad de mercado no sonuna simple contingencia histórica, sino que responden a la estructura lógica de cualquieracción humana; esto es, como si toda acción humana, en cualquier tiempo y lugar, hubiesefuncionado a través de una misma lógica inmutable que coincidía, en lo esencial, con laracionalidad típica de una economía de mercado. Para adentrarnos críticamente en estaproblemática utilizaremos la obra de Karl Polanyi, cuya obra se oponía frontalmente a estasdos tesis manejadas por el liberalismo económico.
Keywords: MISES, Ludwig von; doble movimiento; double movement; economía de mercado; historical teleology; market economy; teleología histórica

Aristóteles Descubre La Economía, Para Temerla. Una Lectura Desde Karl Polanyi - Polo Blanco, Jorge (ARISTOTLE DISCOVERS ECONOMY, TO FEAR IT. A READING THROUGH THE EYES OF KARL POLANYI., 2017)
This study approaches Aristotelian reflections on economy through the eyes of Karl Polanyi, as he resorts to the Greek philosopher to find useful elements when building a profound criticism of the modern market society. Aristotle intuited the uncertain future of a social order devoured by economic relations expanding at a hypertrophic rate. In his time, indeed, this was only a potential threat —he never saw the effective culmination of anything like what we are seeing today—. But he was nevertheless able to see the ultimate meaning of what was at stake, and to understand that the unmeasured, uncontrolled growth of market relations would irremediably affect civic balance. He understood that the unrestricted extension of the desire for profit to all human ties would be a powerful threat to the heart of the political community. (English)
Keywords: Aristotelian economic philosophy; ECONOMÍA DE LA ANTIGUA POLIS; FILOSOFÍA ECONÓMICA ARISTOTÉLICA; ancient capitalism; capitalismo antiguo; economic of ancient polis; market society; sociedad de mercado

Género y cuidados: respuestas sociales e institucionales al surgimiento de la sociedad de mercado en el contexto europeo - Carbonell Esteller, Montserrat; Gálvez Muñoz, Lina; Rodríguez Modroño, Paula (GENDER AND CARE: SOCIAL AND INSTITUTIONAL ANSWERS TO THE DEVELOPMENT OF THE MARKET ECONOMY IN EUROPE., 2014)
This article examines from a care approach the social and institutional responses to the development of the market economy in the European context. Studying this long period -which Polanyi called the double movement- is relevant because it constitutes the historical process by which the interests of the market, the logic of profits and its social and scientific naturalization come to dominate. Since then, the importance of care work in people's life, the reproduction of the labour force, and the provision of welfare and social insurance have been ignored. Until very recently, historical analyses have focused on the emergence of the Welfare State, regardless of how the state's answers interacted or modeled with other spheres of welfare provision, especially the family through women's unpaid work. The article focuses on the European experience and the period analyzed comprehends the disintegration of communal and assistance care with the Old Regime Crisis, the development of charity and associations as solutions to the inhibition of the Liberal State in the 19th century -solutions that were limited and insufficient, leading to the state assumption of the care and assistance functions, embryo of the development of later Welfare States after World War II. (English)
Keywords: capitalismo liberal; care; cuidados; estados del bienestar; gender; género; liberal capitalism; modelos asistenciales pre-industriales; pre-industrial mutual aid regimes; welfare state

Los conceptos más importantes en el trabajo de Karl Polanyi y su relevancia contemporánea - Polanyi Levitt, Kari (Economía y Desarrollo, 2014)
El artículo se centra en la vida y obra del historiador Karl Polanyi, quien escribió el libro "La Gran Transformación", en 2014 y también discute la investigación realizada sobre la vida económica de las sociedades primitivas por Polanyi.
Keywords: Great Transformation, The (Book); primitive societies

Crisis del modelo neoliberal, hacia una planificación regional. Un aporte polanyiano - Valderrama Saud, Paula (Crisis of the Neoliberal Model; Towards Regional Planning - a Polanyian Contribution., 2014)
Using Karl Polanyi's analytical instrument, I argue that the current withdrawal of the industrialized powers and the emergence of alternative policies in Latin America are determined by the crisis of the neoliberal model. The polarity between democracy and the market, observed since the beginnings of liberal capitalism, has deepened since the inter-war period due to the appearance of so-called "mass democracy." Since that period, foreign policies of industrialized countries have derived from social conflict caused by this polarity. Current neoliberalism, which favors the limitation of democracy in favor of the self-regulating global market, is a system that contains inherent contradictions on financial and socio-political levels. These contradictions are the cause of the current crisis in the United States and the European Union, a crisis that favors the beginning of a new era characterized by greater regional planning and a plurality of development paths. (English)
Keywords: European Union; Latin America; crisis; democracia; democracy; globalization; government policy; market; mercado; neoliberalism; neoliberalismo; planificación regional; regional planning

Karl polanyi and the economicist hybris of modernity - Polo Blanco, Jorge (Logos (Spain), 2013)
Using the work of Karl Polanyi as its axis, this study attempts to sketch a criticism of economicism and of the society that produces it, a society launched on a historical cultural path that may well be understood as a gradual economic totalization of human life. That is the critical path which will be posed here, if only in an embryonic manner.
Keywords: economic determinism; economic totalization; economicism

Textos escogidos. Karl Polanyi - Coraggio, J.L. (Buenos Aires : Consejo Latinoamericano de Ciencias Sociales (CLACSO) ; Los Polvorines, Provincia de Buenos Aires : Universidad Nacional de General Sarmiento, 2012)
Contents of book: Primera parte: Karl Polanyi y su obra: Actualidad de Karl Polanyi / Jean-Louis Laville. Karl Polanyi : su vida y época / Marguerite Mendell y Kari Polanyi Levitt. Karl Polanyi y la otra economía en América Latina / José Luis Coraggio -- Segunda parte: Los ensayos de Karl Polanyi: El lugar de las economías en las sociedades (1957) ; La economía como proceso instituido (1957) ; Aristóteles descubre la economía (1957) ; Feudalismo primitivo y feudalismo de la decadencia (1950) ; Marxismo e historia económica (comentario a Maurice Dobb) (1947) ; Comerciantes y comercio (1951) ; Semántica de los usos de la moneda (1957) ; Economía y democracia (1932) ; La esencia del fascismo (1935). El fascismo y la terminología marxista (1934) ; El marxismo redefinido (1934) ; Marx sobre el corporativismo (1934-1937) ; El cristianismo y la vida económica (1934-1937) ; Comunidad y sociedad : la crítica cristiana a nuestro orden social (1937) ; ¿Capitalismo universal o planificación regional? (1945) ; El significado de la democracia parlamentaria (1944-1945) ; Nuestra obsoleta mentalidad de mercado (1947) ; Sobre la creencia en el determinismo económico (1947) ; Jean-Jacques Rousseau o ¿Es posible una sociedad libre? ; La libertad y la tecnología (1955) ; La máquina y el descubrimiento de la sociedad (1957) ; La libertad en una sociedad compleja (1957) ; La sociedad opulenta según Aristóteles (1959).
Keywords: antropología económica; economic anthropology; economic history; economics; economía; historia económica

Discussions around Argentine Capitalism: Economic Debate and Contribution of Karl Polanyi for Our Days - Rossi, Ignacio Andrés (2022)
The article proposes to address the current discussions about national capitalism and the Argentine economy from a set of canonical ideas of the work of Karl Polanyi. Argentina, which for several decades has been going through recurring crises in its economic model, awakens a plurality of voices from social scientists and specialized journalists who debate the problems, limitations and projections of national capitalism. For this, we have surveyed these discussions, to a greater extent, from the specialized press and the recently published bibliography, paying attention to the theoretical, interpretative and ideological proposals that allow us to generate relationships with Polanyi's theory. It was concluded that the latter's ideas about the functioning of capitalism, markets, the State and contemporary social dynamics provide significant conceptual background to frame the current discussions among social scientists about the Argentine economy.
Keywords: Argentina; capitalism; development; stability; state

Requisitos para el cambio transformativo: contribuciones de Karl Polanyi - Kirby, Peadar (International Review of Economic Policy-Revista Internacional de Política Económica, 2020)
Una pregunta clave que surge de la pandemia de coronavirus es qué se requiere para hacer de esta fase temporal un camino hacia el cambio transformador. O, como sucedió en gran medida después de la crisis financiera de 2008, ¿volverá la sociedad a una economía dominada por el crecimiento y cargada de carbono basada en una ética del individualismo radical y el consumismo desenfrenado, informada por recetas neoliberales? Este artículo se basa en el trabajo de Karl Polanyi (1886-1964) para ofrecer un marco teórico alternativo para guiar el cambio social transformador en la era del cambio climático. Comienza por identificar una característica clave del equilibrio entre la estructura y la agencia en la sociedad contemporánea, a saber, un optimismo tecnológico y propone un marco alternativo a través de la economía política. La segunda sección identifica los dos marcos teóricos clave que informaron las configuraciones dominantes de la economía política desde la Segunda Guerra Mundial: un marco socialdemócrata y un marco neoliberal. Se argumenta que ahora es necesario un nuevo marco. La tercera y más larga sección dibuja una gama de contribuciones conceptuales de Polanyi para ofrecer una teoría distintivamente diferente a la que ofrece el neoliberalismo. Estos incluyen: sociedad de mercado; diferentes significados de economía; mercancías ficticias; formas de integración; doble movimiento; descubrimiento de la sociedad; la persona humana y la libertad; y el poder de la tecnología. La sección final saca conclusiones.
Keywords: COVID-19; climate change; market society; neoliberalism

Economía de mercado, globalización y migración: retos y rostros de las personas vulneradas globales. Un análisis desde Karl Polanyi - Franco, Jefferson Frenel Junior Pierrelus (Contextualizaciones Latinoamericanas, 2020)
Este ensayo pretende demostrar cómo el mercado autorregulado que pregonael neoliberalismo es una falacia y que tiende tarde que temprano a acabar odestruir las propias condiciones sociales, ambientales y culturales que aseguranla vida en el planeta. Basado en una globalización financierista, en la privatización yen la liberalización de mercado, ese modelo se ha convertido en la mayor fábrica deempobrecidos, logrando cooptar y subordinar a los Estados a sus designios a travésde las grandes empresas transnacionales e instituciones económicas internacionales.La neo-esclavitud, la miseria, la precariedad y la violencia se han instalado como unmodo de ser y de vivir, aunadas a la emigración, debido a esa explotación, extracciónde recursos naturales a ultranza que lleva a cabo ese modelo económico imperante.Hay voces, manifestaciones, como la de Karl Polanyi, que quieren poner un freno a esemolino satánico, llamado neoliberalismo.
Keywords: economía de mercado; globalización; globalization; market economy; migración; violence; violencia